Eldercare helpline: connecting with older people to mitigate the effects of the Covid-19 crisis in Jaipur, India. Issue 1 (1st July 2021) - Raina, Roshan Lal; Gupta, Asheesh; Gupta, Umesh; Singh, Upasana; Jain, Divanshu
Abstract : Purpose: The purpose of this study is to identify the needs and concerns of older people in Jaipur, Rajasthan, India during the lockdown phase of the Covid-19 crisis. The study also aims to present a viable model for extending needed support through a telephone helpline run by a team of young student volunteers. Design/methodology/approach: The study uses a thematic analysis of the interaction between callers (service users) and volunteers. Findings: The study shows that the main reasons that motivate the use of the helpline are to seek medical advice and to request medical services and medical supplies free of charge. However, the study also shows that other reasons for calling the helpline are feelings of loneliness and the need for psychological support, especially due to insufficient assistance from families. Practical implications: The study shows the benefits of providing this type of service for older people during a time of national health crisis. The service is cost-effective and offers a one-stop assistance point. Social implications: The service also constitutes an avenue for building intergenerational solidarity and empathy between younger and older people. This is especially important for citizens who feel socially isolated and disconnected from the rest of society. Originality/value: The study offers a model for an easily created resource that could usefully be exported to other geographic settings.